2019
DOI: 10.1097/mpg.0000000000002437
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Conventional Milk Versus Milk Containing Only A2 β‐Casein on Digestion in Chinese Children

Abstract: Objectives: In this study, we hypothesized that replacing conventional milk, which contains A1 and A2 β-casein proteins, with milk that contains only A2 β-casein in the diet of dairy or milk-intolerant preschoolers (age 5 to 6 years) would result in reduced gastrointestinal symptoms associated with milk intolerance, and that this would correspond with cognitive improvements. Methods: This randomized, double-blind, crossover study aimed to compare the effects of 5 days’ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 25 publications
3
44
0
1
Order By: Relevance
“…The effects of the milk treatments on GI symptoms may be related to GI effects due to longer transit time in the colon by milk containing A1 β-casein [ 17 ]. A study in Wistar rats and some human clinical trials showed that A1 β-casein increased GI transit time and colonic activity of the inflammatory marker myeloperoxidase [ 17 , 18 , 30 ]. These effects, which were counteracted by the opioid blocker naloxone, might be initiated and mediated by the opioid peptide BCM-7, which is formed after the ingestion of A1 β-casein [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The effects of the milk treatments on GI symptoms may be related to GI effects due to longer transit time in the colon by milk containing A1 β-casein [ 17 ]. A study in Wistar rats and some human clinical trials showed that A1 β-casein increased GI transit time and colonic activity of the inflammatory marker myeloperoxidase [ 17 , 18 , 30 ]. These effects, which were counteracted by the opioid blocker naloxone, might be initiated and mediated by the opioid peptide BCM-7, which is formed after the ingestion of A1 β-casein [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Power calculations indicated that completion of the protocol, with a crossover study design, by 26 subjects would be adequate to demonstrate 80% statistical power, consistent with biological relevance using α = 0.05 to detect a 20% change in breath hydrogen. The sample size for symptoms was derived from a previous study in Chinese preschoolers aged 5 to 6 years [ 18 ]. The COVID-19 pandemic caused us to suspend the study in February 2020 with 25 verified LI subjects and an additional eight maldigesters who did not meet the LI criteria.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several human studies focused on the possible relationship between the consumption of milk containing A1 or A2 beta-casein and milk intolerance. Different randomised crossover studies conducted on subjects with mild-to-moderate milk intolerance observed that A2-milk consumption could attenuate the acute gastrointestinal symptoms by reducing gastrointestinal transit time, lowered the inflammatory state that aggravated lactose intolerance symptoms, caused an increase of faecal SCFA content and improved cognitive performance [ 11 , 12 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The substitution is mainly due to "C" nucleotide with "A" nucleotide in that corresponding nucleotide position (Farrell et al 2011). Moreover, many types of research have given positive correlation between A1 variant of beta casein and health-related problems (Sheng et al 2019).…”
Section: Introductionmentioning
confidence: 99%